2021
DOI: 10.1186/s12872-021-02065-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diurnal temperature range on cardiovascular disease hospital admissions among Chinese farmers in Dingxi (the Northwest China)

Abstract: Background Diurnal temperature range (DTR) has been widely applied in exploring its effect on cardiovascular disease (CVD). However, few studies have investigated the correlations between DTR and CVD in poor rural areas in China. This study aimed to examine the association between DTR and CVD in rural China. Methods A distributed lag nonlinear model was used to evaluate the relationship between DTR and CVD risk among farmers living in the city of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Overall, the results support the previous conclusion that the decreasing DTR is mainly due to the Tmin increasing faster than the Tmax [4,61]. A low DTR can exert adverse health impacts on human beings [10]; it has been observed that the increased occurrence of cardiovascular diseases is more pronounced in females and the elderly than males and adults [62].…”
Section: Seasonal and Annual Dtr Trends Over Nepalsupporting
confidence: 88%
“…Overall, the results support the previous conclusion that the decreasing DTR is mainly due to the Tmin increasing faster than the Tmax [4,61]. A low DTR can exert adverse health impacts on human beings [10]; it has been observed that the increased occurrence of cardiovascular diseases is more pronounced in females and the elderly than males and adults [62].…”
Section: Seasonal and Annual Dtr Trends Over Nepalsupporting
confidence: 88%
“…Under the global warming, the faster increasing nighttime temperature results in less time for human bodies to cool off and contributes to more occurrence of morbidity and mortality (Luo et al 2013). And such expose to DTR changes occurred more easily in the developing countries (Zhai et al 2021).…”
Section: Discussionmentioning
confidence: 99%